Risk Factors of Worsening of Systemic Lupus Erythematosus in Patients at Two Tertiary Hospitals in Jakarta - Aji, Giri; Sudaryo, Mondastri Korib; Djuwita, Ratna; Sukamto, Sukamto (UI Scholars Hub, 2023)
Systemic Lupus Erythematosus (SLE) is a prototypical multiorgan autoimmune disease with a fluctuating and chronic disease course. As an emerging disease in this century, SLE will burden stakeholders and the country. This study was conducted to determine the prognostic factors for SLE worsening, especially in ambulatory patients. This ambispective study used logistic regression to view the risk factors for worsening SLE in patients. Anemia, age, body mass index, education level, employment status, marital status, hydroxychloroquine, and immunosuppressants were the independent variables in this study. This study concludes that anemia is statistically significant and, therefore, a risk factor for worsening SLE in patients (RR = 5.31; p-value